Marine Peptides as Anticancer Agents: A Remedy to Mankind by Nature - Negi, Beena; Kumar, Deepak; S. Rawat, Diwan (Current Protein and Peptide Science, 2017)
Background: In the search of bioactive molecules, nature has always been an important source and most of the drugs in clinic are either natural products or derived from natural products. The ocean has played significant role as thousands of molecules and their metabolites with different types of biological activity such as antimicrobial, anti-inflammatory, anti-malarial, antioxidant, anti HIV and anticancer activity have been isolated from marine organisms. In particular, marine peptides have attracted much attention due to their high specificity against cancer cell lines that may be attributed to the various unusual amino acid residues and their sequences in the peptide chain. This review aims to identify the various anticancer agents isolated from the marine system and their anticancer potential. Method: We did literature search for the anticancer peptides isolated from the different types of microorganism found in the marine system. Total one eighty eight papers were reviewed concisely and most of the important information from these papers were extracted and kept in the present manuscript. Results: This review gives details about the isolation, anticancer potential and mechanism of action of the anticancer peptides of the marine origin. Many of these molecules such as aplidine, dolastatin 10, didemnin B, kahalalide F, elisidepsin (PM02734) are in clinical trials for the treatment of various cancers. Conclusion: With the interdisciplinary and collaborative research and technical advancements we can search more promising and affordable anticancer drugs in future.
Keywords: dolastatin 10